(3QSGdI EjVGM GdJhMjO def JfHg ef SfI GdZadI hYQa GdMb hCHUQ hEKHGJ GdMLIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce GdPi CfcQ hLhOg ddZGUHhf GdeaJQhf GdTGchf GdedMOhf hJhSdJ Edjg Hhdi Mbg s
(3BNQgG (B:s
(3Ef gPG dgh GdbUU GdMb heG ef Edg EdG Gddg hCf Gddg gh GdYRjR GdMcje ef Sfjf bGFe GdReGf GdBNP GdMb ef GdeTQcjf hGdLGMOjf hCgd GdfaGb hGdWZjGf fLRJ HefI hdi GdCeQ bhHdJ hUMJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B73s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3abg GdePGgH GdCNQis